Crop-residue management for increased wheat (Triticum aestivum) production under saline soils of arid fringes - Regar, P L; Rao, S S; Vyas, S P (The Indian Journal of Agricultural Sciences, 2005)
Cyprinus carpio communis L., Hypophthalmichthys molitrix Val. and Puntius gonionotus Bleeker) worth Rs 9130 were harvested and another 0.193 tonne of under-size fish (Catla catla Hamil., Labeo rohita, Cirrhinus mrigala, Labeo bata, Cyprinus carpio communis, Hypophthalmichthys molitrix and Puntius gonionotus) worth Rs 6000 were left for further rearing. Net returns from fishery component were Rs 8530, being similar to 3 rice crops grown in a sequence. Net returns from vegetables and ornamental crops were Rs 425.